Multifaceted Displacement and Trauma in McCormick’s Sold: A Critical Examination of Young Adult Trafficking - Thapa, Hukum (Bon Voyage, 2025)
This study explores the multifaceted displacement of young adult in Patricia McCormick’s Sold from traumatic perspectives focusing on girl trafficking in Nepal. It examines why Young adult protagonist Lakshmi faces displacement, what types of displacement she encounters, and how she overcomes these traumatic experiences. This paper argues that Sold projects physical, emotional, psychological, cultural, social, economic, moral and ethical displacement of young adult protagonist Lakshmi. It argues that Lakshmi like young adult faces multifaceted displacement because of economic hardship, social and cultural practices, betrayal and deception, and lack of agency. This research reveals that Lakshmi’s displacement has devastating impact like loss of innocence, psychological trauma, social alienation, erosion of identity, disconnection from cultural roots, economic exploitation, diminished future prospects, resilience and survival instincts and potential for redemption and recovery. It primarily focuses on the trauma Lakshmi confronted and ways of incapacitating the trauma. For that purpose, it employs the perspectives of Cathy Caruth’s Trauma as unclaimed experience and Dominic LaCapra’s psychological trauma. Ultimately, it hopes to pave the way for additional research on a range of topics related to girl trafficking in Nepal, South Asia, and other countries.